Les intermittents du spectacle. Sociologie d'une exception - D'Amours, Martine (Relations industrielles / Industrial Relations, 2008)
The article reviews the book, :Les intermittents du spectacle. Sociologie d’une exception," by Pierre-Michel Menger.
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z